The Effect of Compound Exercises on Added Weights on Some Skill Abilities in Youth Soccer Players Aged 17 – 19 Years Old - Hashem, Hesanain; Qasem, Sabah (Journal of Physical Education, 2021)
The study aimed at designing compound exercises using added weight on some skill abilities in youth soccer players aged (17 – 19) years old. The researcher sued the experimental method on (30) players aged (17 – 19) years old from Al Zawraa Sport Club. The subjects were divided into three groups and the training program was applied for (8) weeks with (3) training sessions per week. The data was collected and treated using proper statistical operations to conclude that compound exercises with weights between improved the subjects compared to the groups that did not use the added weights. Finally, the researchers recommended the necessity of using compound exercises using added weights during training sessions for youth soccer players.